2017
DOI: 10.1103/physrevb.96.235202
|View full text |Cite
|
Sign up to set email alerts
|

Interband absorption edge in the topological insulators Bi2(Te1xSex)3

Abstract: We have investigated the optical properties of thin films of topological insulators Bi2Te3, Bi2Se3 and their alloys Bi2(Te1−xSex)3 on BaF2 substrates by a combination of infrared ellipsometry and reflectivity in the energy range from 0.06 to 6.5 eV. For the onset of interband absorption in Bi2Se3, after the correction for the Burstein-Moss effect, we find the value of direct bandgap of 215±10 meV at 10 K. Our data supports the picture that Bi2Se3 has a direct band gap located at the Γ point in the Brillouin zo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 50 publications
6
29
2
Order By: Relevance
“…The studied Bi 2 Te 3 epilayer with a thickness of 300 nm was grown using molecular beam epitaxy on a 1-mm-thick (111)-oriented cleaved BaF 2 substrate [38,39]. The details about the growth technique and the sample characterization were presented previously [27]. The Hall measurements at liquid-helium temperature, performed on the same sample as all our optical and magneto-optical studies, indicate ptype conductivity and a moderate hole density of p ∼ 2 × 10 18 cm −3 .…”
Section: Sample Preparation and Experimental Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studied Bi 2 Te 3 epilayer with a thickness of 300 nm was grown using molecular beam epitaxy on a 1-mm-thick (111)-oriented cleaved BaF 2 substrate [38,39]. The details about the growth technique and the sample characterization were presented previously [27]. The Hall measurements at liquid-helium temperature, performed on the same sample as all our optical and magneto-optical studies, indicate ptype conductivity and a moderate hole density of p ∼ 2 × 10 18 cm −3 .…”
Section: Sample Preparation and Experimental Detailsmentioning
confidence: 99%
“…This implies either none or double valley degeneracy, * milan.orlita@lncmi.cnrs.fr with the minimum at the (Z) point or on the -Z line, respectively. In optical experiments [21][22][23][24][25][26][27][28], both direct and indirect band gaps were reported with widths not exceeding 200 meV. Available theoretical studies provide us with diverse views on the electronic bands in Bi 2 Te 3 [8,[29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…At some composition, the valley near the Γa line and f valence band edge must cross the Γ/z and this may be the origin of the band gap peak. Recent interband absorption studies on this alloy system have found that at Bi 2 Te 2 Se, there is a change in the location of the lowest energy direct transition [55]. This may be a switch from the VB f to CB f transition in x < 1 to the VB Γ/z to CB Γ/z for x > 1.…”
Section: Electronic Structurementioning
confidence: 90%
“…This has been attributed to the crossing in energy with composition of two N v = 6 valence bands [13]. In the n-type alloy system, there is a peak in the band gap with alloy composition very near Bi 2 Te 2 Se and also a peak in Seebeck effective mass of 1.30 m e near Bi 2 Te 2.5 Se 0.5 ( Figure 2) [1,4,5,8,[53][54][55]. As the compositions for two peaks do not coincide, the transport behavior cannot be described by a simple crossing of two conduction bands and a more detailed investigation is required.…”
Section: Electronic Transportmentioning
confidence: 99%
“…8 This has motivated extensive studies of electromagnetic properties of TI chalcogenide crystals over a broad range of frequencies from THz to UV. [9][10][11][12][13][14][15] Interaction of electromagnetic waves with the topological surface states can be enhanced by suitably structuring the TI crystals with subwavelength units, such as resonant metamolecules, giving rise to absorption and localization of the electromagnetic field. TI metamaterials have been realized at THz and UV-visible frequencies, 9,[16][17][18] however there have been hardly any studies on resonant TI structures at intermediate near-and mid-infrared frequencies, where the compositionally tunable refractive index is extremely high, 19 and optical conductivity from charge carriers in topological surface states becomes significant.…”
mentioning
confidence: 99%